It is a painful somatic symptom, not the history of cancer/malignancy that is associated with depression: findings from multiple national surveys. Issue 4 (April 2017) - Johnson, Krystina; Politis, Maria D.; Hansen, Andrew R.; McKenzie, Lindsey E.; Duncan, Dustin T.; Zhang, Jian
Abstract : Abstract: Medical case management has improved in the past few decades, changing the dynamic interaction between depression and prevalent medical diseases. It is relevant to describe the comorbidity between depression and medical diseases to further improve the effectiveness of case management. We analyzed the data of adults aged 20 years and older, who completed depression screening as a part of the National Health and Nutrition Examination Survey, 2005 to 2012. Depression was ascertained using the Patient Health Questionnaire, a 9-item screening instrument asking about the frequency of depression symptoms over the past 2 weeks. Comorbid diseases were assessed in a self-reported personal interview on doctor-diagnosed health conditions. The associations between depression and medical diseases were limited to the diseases with painful somatic symptoms. Reported from 19.78% of men and 27.84% of women, arthritis was the most prevalent chronic disease, and was the only one consistently associated with depression. The odds ratio of moderate to severe depression was 1.65 (95% confidence interval = 1.12-2.44) for men and 2.11 (1.63-2.99) for women with arthritis compared with their counterparts free of arthritis. Moderate/severe depression was associated with a history of heart disease among men (2.45 [1.19-5.06]) and angina/angina pectoris among women (2.13 [1.07-4.26]). No associations were found between depression and cancer/malignancy, either among men or women. The potential impact of pain management on depression prevention among general population is substantial; more efforts are needed to assess chronic pain to facilitate timely prevention and treatment of depression and comorbid medical conditions. Abstract : Supplemental Digital Content is Available in the Text.The recent national surveys show it is chronic medical illness featuring painful somatic symptoms, especially, arthritis, and not cancer/malignancy that was significantly associated with depression.